Humidifier fever (1977)
MRC Symposium (1977).Thorax, 32, 653-663. Humidifier fever. In enclosed environments, it may be necessary to regulate temperature, ventilation, and humidity to maintain comfortable working conditions. Several systems can be used although in terms of installation and running costs a simple radiator system is far more economical than air conditioning with complete temperature and humidity control. Humidity control requires the introduction of water into a moving current of air, and in such a system baffle plates are often used to eliminate large droplets; also any unused water is usually recirculated. Organic dust drawn into the system and settling on the baffle plates and in the mixing chamber may be utilised by micro-organisms introduced from the atmosphere and from the water supply, and a biomass builds up. Microbial material is then voided into the working atmosphere by the ventilation system. Under appropriate exposure conditions susceptible individuals may succumb to an episode of humidifier fever, an influenza-like illness with pyrexia and malaise as the main symptoms, but cough, chest tightness, dyspnoea and weight loss may also be seen. The episodes usually occur after absence from work for a few days and have been termed `Monday sickness'. Individuals are often able to return to work the next day and appear refractory to further exposure. The disease is of the winter months probably due to the larger amount (up to 90%) of fresh air drawn into the humidifier during the summer. In the blood of exposed subjects precipitins are usually present to extracts of baffle plate material and recirculating water although they are not necessarily indicative of disease. Skin tests may be positive and inhalation challenge has reproduced the disease in susceptible individuals. Many organisms may be isolated from baffle plates and recirculating water but only amoeba extracts have produced consistently positive reactions with sera from affected individuals. Remedial actions such as changing from water to steam humidification or running recirculation water to waste have proved effective in some factories. Other measures may be considered, for example, adding microbicidal agents or prefiltering intake air. The pyrexial episode may be due to immune complex-complement or alternative pathway-complement activation, inducing the release of leucocyte pyrogen; alternatively, sensitised lymphocytes can release lymphokines capable of inducing leucocyte pyrogen release.